Path Optimization For Cooperative Multi-Head 3d Printing - Cheong, Kah Jun (2020)
In 3D printing, reducing the time needed to print an object is desirable. The print time of an object is largely influenced by the length of the path that the nozzle of the 3D printer takes for each layer (also called the travel distance). Hence, finding the best path for the nozzle is termed as the Layer Path Optimization Problem (LPOP). Previous authors have shown that the LPOP can be defined in terms of the Undirected Rural Postman Problem (URPP), a known problem in graph theory. Two well-known algorithms for solving a closely related graph theory problem known as the Travelling Salesman Problem (TSP) are the Ant System (AS) and Ant Colony System (ACS) algorithms. Therefore, to solve the LPOP, two algorithms are proposed, the modified AS algorithm and the modified ACS algorithm. These two proposed algorithms have been modified from the original algorithms in order to solve the URPP instead of the TSP. The performance of the two proposed algorithms is compared against Cura, which is a commonly used software for generating the nozzle path. The obtained results show that both the modified AS and ACS algorithms were able to perform better than Cura in terms of both travel distance and print time for a variety of different 3D models.